2011
DOI: 10.1007/s12011-011-9222-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bulk and Nanosized Titanium Dioxide (TiO2) on Wheat Seed Germination and Seedling Growth

Abstract: The impacts of different concentrations of bulk and nanosized TiO(2) on seed germination and seedling growth of wheat were studied in a randomized completely design with four replications in the College of Agriculture, Ferdowsi University of Mashhad, Iran, in 2011. The experimental treatments included five concentrations of bulk (1, 2, 10, 100, and 500 ppm), five concentrations of nanosized TiO(2) (1, 2, 10, 100, and 500 ppm), and control (without any TiO(2)). Results indicated that among the wheat germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(118 citation statements)
references
References 16 publications
10
105
1
2
Order By: Relevance
“…To the best of our knowledge, there is no report on the application of TiO 2 NPs to enhance C. fistula seed germination or seedling growth. Feizi et al (2012) found similar results for wheat seed germination. They showed that the treatment of wheat seeds with bulk and nanosized TiO 2 could not significantly enhance germination percentage and rate compared to control but the nanosized TiO 2 increased shoot and seedling lengths at 2 and 10 ppm concentrations which was higher than those of the untreated control and bulk.…”
Section: Discussionsupporting
confidence: 67%
“…To the best of our knowledge, there is no report on the application of TiO 2 NPs to enhance C. fistula seed germination or seedling growth. Feizi et al (2012) found similar results for wheat seed germination. They showed that the treatment of wheat seeds with bulk and nanosized TiO 2 could not significantly enhance germination percentage and rate compared to control but the nanosized TiO 2 increased shoot and seedling lengths at 2 and 10 ppm concentrations which was higher than those of the untreated control and bulk.…”
Section: Discussionsupporting
confidence: 67%
“…Miralles et al (2012) studied the phytotoxicity of wheat and alfalfa using industrial CNT and catalytic impure CNT and found that there was no toxic effect on germination under high concentration. Feizi et al (2012) found the positive effect on the germination and seedling of wheat when treated with different concentrations of bulk and nanosized TiO 2 . Recently, we reported a study on dicotyledonous plant gram (Cicer arientinum) using water soluble CNT which was synthesized from Mustard oil soot and thus did not contain any trace amount metal impurity and found that it enhances the growth of the gram plant (Tripathi et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Over last few years, there have been extensive studies to understand the influence of nanomaterials on the growth of different types of plants (Khodakovskaya et al 2009;Khodakovskaya et al 2013a, b;Lu et al 2002;Cañas et al 2008;Yang et al 2006;Hong et al 2005a, b;Tan et al 2009;Yuan et al 2011;Khodakovskaya et al 2013a, b;Mahajan et al 2011;Wang et al 2012;Larue et al 2012;Miralles et al 2012;Feizi et al 2012;Tripathi et al 2011;Sonkar et al 2012). Khodakovskaya et al (2009Khodakovskaya et al ( , 2013a demonstrated that at very low doses MWCNT can penetrate the seed coat and enhance the germination of tomato plant.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TiO 2 has opened new and interesting horizon for plant physiologists in order to improve plant performance even under stress conditions. Since, the effects of TiO 2 NPs may not be the same in all environmental conditions and would be vary between different plant species and applied concentrations (Feizi et al, 2012). Thus, in the present research the influences of TiO 2 NPs concentrations on morpho-physiological and biochemical characteristics of dragonhead, as an aromatic and medicinal plant, were investigated under both water stress and non-stress conditions.…”
Section: Introductionmentioning
confidence: 99%